Home Firm Performance after Foreign Investments and Divestitures - Dirk Engel; Vivien Procher (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Being international' has nearly become an undisputed aim for firms in a globalized world. Several papers find a positive relationship between foreign direct investment (FDI) and the home performance of firms. In this paper we address the 'FDI - export' relationship to better understand this pattern. Furthermore, by presenting first results on firm's post-divestiture employment growth at home we are able to provide a more comprehensive view on fi rm performance after stepping in and out of foreign markets. We apply a propensity score matching technique in combination with a difference-in-difference estimator to analyze the performance dynamics of French firms that invested abroad or carried out foreign divestitures during the period 2000-2007. FDI has on average a positive home firm eff ect in terms of export share, operating turnover and employment. Industry differences reveal that firms in high-tech industries experience a strong increase in their home performance, whereas firm performance in low-tech industries increases only moderately in post-investment periods. In contrast, the divestiture impact on the post-divestiture performance is rather negligible. – – Der Artikel untersucht die Entwicklung des Firmenerfolgs von französischen Firmen im Heimatmarkt nach ausländischen Markteintritts- und Marktaustrittsentscheidungen im Zeitraum 2000-2007. Hierzu wird ein Propensity Score Matching Verfahren in Kombination mit einem Differenzen-in-Differenzen Schätzer angewandt. Firmen, die erstmalig einen ausländischen Markt über Direktinvestitionen betreten, verfügen im Durchschnitt in den Folgejahren über höhere Exportintensität, Umsatzentwicklung und Beschäftigungswachstum als vergleichbare Firmen, die zum selben Zeitpunkt nicht ins Ausland gegangen sind. Insbesondere Firmen aus Hochtechnologiebranchen profitieren von einer überproportional positiven Firmenentwicklung im Heimatmarkt. Im Gegensatz dazu wirkt sich ein Rückzug aus ausländischen Märkten nur geringfügig auf die Unternehmensentwicklung im Inland aus.
Keywords: F21; F23; D21; L25; 330; Foreign markets; entry and exit; firm performance; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Direktinvestition; Desinvestition; Außenhandelswirtschaft; Unternehmensentwicklung; Beschäftigungseffekt; Marktanteil; Umsatz; Frankreich